Progress towards elimination of trans-fatty acids in foods commonly consumed in four Latin American cities - Monge Rojas, Rafael (2017)
Objective To assess progress towards the elimination of trans-fatty acids (TFA) in foods after the 2008 Pan American Health Organization (PAHO) recommendation of virtual elimination of TFA in Latin America. Design A descriptive, comparative analysis of foods that were likely to contain TFA and were commonly consumed in four cities in Latin America. Setting San José (Costa Rica), Mexico City (Mexico), Rio de Janeiro (Brazil), Buenos Aires (Argentina). Subjects Foods from each city were sampled in 2011; TFA content was analysed using GC. TFA of selected foods was also monitored in 2016. Results In 2011-2016, there was a significant decrease in the content of TFA in the sampled foods across all sites, particularly in Buenos Aires (from 12·6-34·8 % range in 2011-2012 to nearly 0 % in 2015-2016). All sample products met the recommended levels of TFA content set by the PAHO. TFA were replaced with a mixture of saturated and unsaturated fats. Conclusions Our results indicate a virtual elimination of TFA from major food sources in the cities studied. This could be due to a combination of factors, including recommendations by national and global public health authorities, voluntary and/or mandatory food reformulation made by the food industry.